PELATIHAN KOMUNIKASI DAN BUSINESS WRITING BAGI ANAK BINA LULUSAN SMU/SMK DI PALMERAH DAN BIDARACINA- JAKARTA - Christine Winstinindah Sandroto (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Often occurs high school/vocational high school graduates are difficult to find a job. For this reason, FEB-UAJ cooperates with YBP to provide Communication and Business Writing training for high school/vocational high school graduates who are under YBP's supervised in Palmerah and Bidaracina-Jakarta. The purpose of this training is to prepare participants to enter the workplace and encourage them to continue to study in Higher Education. The training consist of three stages: preparation, implementation, and evaluation. Training methods with lectures, discussions, questions and answers, practice, role-play, games, and ice breaking, all of are tailored participant's ability. The results of the training evaluation showed that the participants were satisfied with training materials, the facilitators, and the organization of the training, and very satisfied with training facilities provided by the UAJ campus. The material subject given is appropriate to prepare participants in the workplace. In the next project, training evaluation will be completed with pre and post-test and assistance for participants in the process of finding a job. Training methods will also be made more varied and consider the use of technology in learning. This training material can be supplemented by preparation on how to become entrepreneurs.